Evaluation of the piezoelectric behaviour produced by a thick-film transducer using digital speckle pattern interferometry - Tendela, Lucas Pedro (2011)
This paper presents an interferometric measurement of the out-of-plane deflections produced by a piezoelectric transducer, manufactured by thick-film deposition of a ceramic paste over an alumina substrate, when is subjected to a DC electric voltage. It is shown that a digital speckle pattern interferometer with an incorporated phase-shifting facility allows the measurement of nanometer displacements generated by the piezoelectric device. These measurements are used to evaluate the effective piezoelectric charge constant along the polarization direction (d33)eff that characterizes the thick-film transducer.